Royal pains. Season two [videorecording (DVD)] - Feuerstein, Mark; Costanzo, Paulo, 1978-; Flint, Jill; Shetty, Reshma; Scott, Campbell; Rauch, Michael; Penn, Matthew (Universal Studios Home Entertainment, 2016)
Meet Dr. Hank Lawson, young, brilliant, and recently fired from his ER in Brooklyn for all the wrong reasons. Through a twist of fate, he now finds himself the newest 'concierge doctor' in the Hamptons. Providing round-the-clock house calls to the community's rich and famous might be lucrative, but it's not without its challenges and frustrations.